Long‐term events following catheter‐ablation for atrial fibrillation in heart failure with preserved ejection fraction. (27th July 2022) - Ishiguchi, Hironori; Yoshiga, Yasuhiro; Shimizu, Akihiko; Ueyama, Takeshi; Fukuda, Masakazu; Kato, Takayoshi; Fujii, Shohei; Hisaoka, Masahiro; Uchida, Tomoyuki; Omuro, Takuya; Okamura, Takayuki; Kobayashi, Shigeki; et al.
Abstract: Aims: Data regarding prognostic events following catheter ablation (CA) for atrial fibrillation (AF) in patients with heart failure with preserved ejection fraction (HFpEF) are scarce. We conducted this study to compare the incidence of major adverse clinical events (MACE) following CA for AF between patients with HFpEF and those with systolic heart failure (HF). Methods and results: This single‐centre observational study included 142 patients with HF who underwent CA for AF (median follow‐up: 4.0 [2.6, 6.3] years). The patients were grouped based on the presence of HFpEF ( n = 84) and systolic HF (left ventricular ejection fraction <50%, n = 58). We compared the cumulative incidence and incidence rate of MACE, comprising all‐cause death, unplanned cardiovascular hospitalization (CVH), and HF hospitalization (HFH) between both groups and the number of HFH before and after CA in each group. Multivariate analysis was performed to identify the predictors of MACE in patients with HFpEF. The incidence of MACE was comparable between the groups (following the first procedure: HFpEF: 23%, 4.7/100 person‐years, vs. systolic HF: 28%, 6.6/100 person‐years, P = 0.18; last procedure: 20%, 4.8/100 person‐years, vs. 24%, 6.9/100 person‐years, P = 0.21). Although the incidence of HFH was lower in patients with HFpEF than in those with systolic HF (first procedure: 14%, 2.9/100 person‐years, vs. 24%, 5.7/100 person‐years, P = 0.07; last procedure: 11%, 2.5/100 person‐years, vs. 24%, 6.9/100 person‐years, P = 0.01), the incidence of CVH was higher (first procedure: 8%, 1.7/100 person‐years, vs. 5%, 1.2/100 person‐years, P = 0.74; last procedure: 6%, 1.4/100 person‐years, vs. 2%, 0.5/100 person‐years, P = 0.4). The number of HFH significantly decreased in both groups after CA (HFpEF: 1 hospitalization [the first and third quartiles: 0, 1] in pre‐CA, vs. 0 hospitalizations [0, 0] in post‐CA, P < 0.0001; systolic HF: 1 hospitalization [0, 1], vs. 0 hospitalizations [0, 0], P < 0.005). The proportion of HFH among total clinical events was significantly smaller in patients with HFpEF than in those with systolic HF (following the first procedure: 56% vs. 88%, P < 0.005; last procedure: 52% vs. 92%, P < 0.005). Conclusions: CA for AF could be beneficial for patients with HFpEF, similar to those with systolic HF. However, clinical events other than HFH should be considered cautiously in such patients.